Internal and External Factors of Consumer Behaviour: Phenomenon in Buying Decisions at the Keboen Rodjo Restaurant, Kediri - Sri Aliami; Samari; Faisol (Efektor, 2022)
R A restaurant is a business that sells goods and services. The fact shows the restaurant business competition is very tight. The management team needs to be equipped with an understanding of consumer behavior as an influencing factor in decision-making, both internally and externally. In fact, consumer behavior analysis rarely gets the attention of companies. The companies tend to focus on aspects of the marketing mix and customer service. The manager of a company can use it as a reference by understanding the reasons consumers buy to solve the company’s problems. The study aimed to analyze the influence of internal and external factors on consumer behavior both separately and together on purchasing decisions at Keboen Rodjo Kediri Restaurant. Internal factors of consumer behavior include personality, motivation, self-perception, learning, and self-concept. While external factors include culture, social class, reference groups, and family. Purchase decisions are characterized by product selection, brand choice, dealer choice, visit time, and the number of purchases. The research population is all consumers at Keboen Rodjo Kediri Restaurant. The research sample is 60 respondents with an accidental sampling technique. Data were collected through a questionnaire using multiple linear regression analysis techniques. The results of the study prove that internal and external factors have a significant effect separately or jointly on purchasing decisions.